Impact of Government Health Expenditure on Maternal Mortality: An Appraisal of South-Asian-Economies - Azhar Jan; Meenakshi Gupta; Sheikh Aftaab-Ul-Maroof (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2025)
Maternal and child healthcare is a crucial dimension in healthcare delivery. A significant portion of government health expenditure is kept for improvement in infrastructure, service delivery and financial protection to reduce mortality and improve maternal healthcare. The current study aims at assessing the relationship between government health expenditure and maternal mortality in the South Asian context while considering expected years of schooling, fertility rate, government effectiveness, and gross domestic product as control variables. The retrospective panel data has been used from 2002 to 2020 for 8 South Asian Economies. Fixed-effect-model, Pooled-ordinary-least-square, Random-effect-model, Hausman-Test, Fully-Modified-Least-Square and Dynamic-Ordinary-Least-Square techniques have been applied for estimation. The results reveal that government health expenditure is negatively related to maternal mortality across all applied analytical models. The study concludes that a rise in government healthcare expenditure in South Asia can reduce maternal mortality.